PENERAPAN MODEL PROJECT BASED LEARNING UNTUK MENINGKATKAN KREATIVITAS DAN PRESTASI BELAJAR - Misradewi (UNIB Press, 2024)
This study aims to describe the application of the Project Based Learning model to increase creativity and student achievement. The research that was conducted was Classroom Action Research and continued with quasi-experimental research. Classroom Action Research was carried out in three cycles, each cycle going through the stages of planning, implementation, observation and reflection. The research subjects were seventh grade students of SMP Negeri 1 Mulak Sebingkai Lahat. The instruments used are observation sheets and test sheets. The technique of collecting data was by observing and testing, while the experimental class only tested the Project Based Learning model. Data analysis was performed using the t test and the classical mean value. Based on the data analysis of this study, it was concluded that (1) the application of the Project Based Learning model could increase students' creativity; (2) The application of the Project Based Learning model can improve student achievement; (3) There is an effective use of the Project Based Learning model to improve student achievement in social studies subjects for class VII at SMP Negeri 1 Mulak Sebingkai Lahat